Relationship between distortionary agricultural trade policies and food security in developing countries: a causal analysis - Mohamed, Shaheera; Khalid, Haniza (Global Academic Excellence, 2018)
In an increasingly globalised world, agricultural trade and food security inevitably goes hand in hand. On paper, the idea of free agricultural trade continues to be a contentious one as opinions remain divided whether it can lead to greater access and variability of food to a larger number of people or whether it ends up exacerbating hunger and environmental degradation in the developing world by reinforcing pre-existing inequities in the global trading system. In practice, countries tend to intervene in food trade to protect domestic producers from volatilities in international markets, as most obviously seen in 2007-2008. Empirical evidence is mixed regarding the impact distortionary agricultural trade policies have on food security, particularly for developing countries. This study examines the issue using long panel data from 24 developing countries from 1990-2010. The Generalised Propensity Score (GPS) method, a non-parametric matching technique with continuous treatment, is used to assess the effect of Nominal Rates of Assistance (NRA) on the four dimensions of food security; food access, food availability, food utilization and food stability. While it is found that the relationships can be statistically proven, the numbers point to a positive link between distortionary trade policies and food security levels for the majority of these countries. Nonetheless, prolonged and widespread price insulations will ultimately push up global prices, offsetting their domestic food security benefits and distract or slow down the much-needed structural improvements in the country’s agricultural sector.